Case Report: From absolute uterine factor infertility (AUI) to motherhood: the crucial role of psychosocial assessment in the first Italian uterus transplantation case - Pistorio, Maria Luisa; De Pasquale, Concetta; Veroux, Massimiliano; Giaquinta, Alessia; Giambra, Martina Maria; Grasso, Antonino; Scollo, Paolo; Quattropani, Maria Catena Ausilia; Veroux, Pierfrancesco (Frontiers in Psychology, 2026)
IntroductionUterus transplantation represents a revolutionary breakthrough for women with absolute infertility of uterine origin, offering them the possibility of realizing the dream of motherhood. This complex procedure has profound medical, ethical, and psychological implications. The aim of our study was to assess the personality, the presence of anxiety and depression, and perceived quality of life in a 29-year-old woman affected by Rokitansky syndrome (MRKH). Furthermore, we hypothesized that projective tests, compared with quantitative assessments, could more easily uncover the deepest, unconscious psychic contents of this woman who has faced such a difficult journey.DesignDescriptive Longitudinal Study.SubjectsSingle case.Main outcome measuresThe case report follows the Case Reporting (CARE) guidelines. In the pre-transplant evaluation, Giorgia (not her real name) was administered the Machover Test, the Baum Test, the Million Clinical Multiaxial Inventory- III (MCMI-III), the Short Form Health Survey-36 (F-36), the Patient Health Questionnaire-9 (PHQ-9), and the General Anxiety Disorder-7 (GAD-7). The same instruments were re-administered 1 year and 2 years after the birth of her baby girl.ResultsThe projective graphic tests highlighted some significant aspects: the facial expression of the female figure became more restless in subsequent evaluations, until aggressiveness emerged (clenched fists) in the last evaluation. The tree was also drawn on a flowerbed in the last evaluations, indicating a sense of loneliness and abandonment.ConclusionOverall, uterus transplantation appears to be psychologically well-tolerated, but ongoing evaluation and psychological support are essential.